Plant and bacterial nanocellulose: production, properties and applications in medicine, food, cosmetics, electronics and engineering. A review - de Amorim, Julia Didier Pedrosa; de Souza, Karina Carvalho; Duarte, Cybelle Rodrigues; da Silva Duarte, Izarelle; de Assis Sales Ribeiro, Francisco; Silva, Girlaine Santos; de Farias, Patrícia Maria Albuquerque; Stingl, Andreas; Costa, Andrea Fernanda Santana; Vinhas, Glória Maria; Sarubbo, Leonie Asfora (Environmental chemistry letters, 2020)
Cellulose is the main structural component of plant cell walls. Cellulose is a fibrous, water-insoluble substance and is considered to be the most abundant bio-derived polymer on earth. From an industrial perspective, plant cellulose has been the mainstay of the wood industries for the past 100 years. The hierarchical organization and semicrystalline nature of cellulose found in plant fibers allows the extraction of nanofibers and nanocrystals using mechanical and chemical top-down de-structuring strategies. Bacterial cellulose has also been increasingly investigated. Bacterial cellulose is composed of cellulose nanofibers secreted extracellularly by some bacteria; bacterial cellulose is therefore obtained using bottom-up synthesis. The unique nanofibrillar structure of bacterial cellulose confers excellent physical and mechanical properties such as high porosity, high elastic modulus and high crystallinity. Research on nanocellulose is accelerating due actual fossil fuel issues such as CO 2 emissions, plastic pollution and lack of renewable energy. Nanocellulose materials are non-toxic, biodegradable and recyclable, with no adverse effects on health and the environment. Here, we review cellulose production methods, properties and applications, focusing on the food industry, biomedical materials and electronic devices. We compare vegetal nanocellulose and bacterial cellulose. The increase in the number of publications on nanocellulose is also discussed.